(untitled) (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstract: After the fall of the authoritarian regime on April 9, 2003, actual steps began to initiate the political development process, or at least to approach its contents and principles; in order to overcome the failures in the political, economic and social system in a manner consistent with the principles of democracy, human rights and the protection of rights and freedoms. Initiating political development in Iraq required taking steps towards modernizing the structures and basic foundations of the state and community institutions to work on organizing institutional structures and motivating citizens to participate effectively in change through reforms and developing and organizing the relationship with the authorities on the basis of modernization theories to confront pressures and challenges. This arduous process is a complex, ongoing process, not a phased one that can be easily reached and extends over multiple stages. Keywords: Political development, Political quota, political stability, political participation.